Social Support and Diabetes Management Among Older American Indians - Goins, R. Turner; Grant, Molly K.; Conte, Kathleen P.; Lefler, Lisa (Frontiers in Public Health, 2022)
Objective: Identifying the components of social relationships that can facilitate or impede type 2 diabetes (T2D) management and control among older American Indians is an overlooked, yet urgently needed strategy. Thus, we examined social support among older American Indians in relation to their T2D management. Methods: During the fall 2015, we conducted qualitative interviews with 28 participants aged ≥ 60 years who were members of a federally-recognized tribe. Drawing upon the buffering and direct effects theoretical models of how social support affects health, we examined transcribed audio recordings of the interviews with a systematic text analysis approach. We used a low-inference qualitative descriptive design to provide a situated understanding of participants’ life experiences using their naturalistic expressions. Results: The mean age of our participants was 73.0 ± 6.4 years with a mean HbA1c of 7.3 ± 1.5. Main social support sources were family, clinicians/formal services, community/culture, and spiritual/God. All four common social support types were represented, namely emotional, instrumental, informational, and appraisal support with most being instrumental in nature. A prominent gender difference was seen with respect to men receiving more instrumental support family/friends support than women. Discussion: Value orientations among American Indians often reflect extended social systems and interdependence. A deeper understanding is needed of how social relationships can be better leveraged to aid in effective T2D management among older American Indians. The development and implementation of evidence-based social network interventions with an assets-based orientation that build upon the cultural value of reciprocity hold promise to improve T2D outcomes of older American Indians.